Source-based Research of Educational Issues of the EuropeanRenaissanceEpoch: Peculiarities, Approaches, Methods of the Investigating Process - Borys God (Pedagogical Discourse, 2013)
The article deals with the issue of the source based background role and place of any historical and pedagogical research. The author shares his own experience on the topic «Education and upbringingin the epoch of the European Renaissance.» It is confirmed that it is necessary to involve not only the work of leadings theorists of pedagogy, but also a wide variety of sources by nature (written and physical) for a authentic picture of the problem. All these basic points reflect the mentality of the time, its culture , national traditions of education and upbringing, beliefs and so on. The need for an interdisciplinary approach to historical and educational science is emphasized. Interesting and unusual considerations are made on how to work with sources. They are seen as a dialogue between the two cultures of teaching ,which requires imagination, empathy, «lead-in» in the appropriate historical and educational situation.